2012
DOI: 10.1002/pbc.24117
|View full text |Cite
|
Sign up to set email alerts
|

CD133 marks a myogenically primitive subpopulation in rhabdomyosarcoma cell lines that are relatively chemoresistant but sensitive to mutant HSV

Abstract: Background Rhabdomyosarcoma (RMS) is characterized by features of skeletal muscle and is comprised of two major histological subtypes, embryonal (E-RMS) and alveolar (A-RMS). Subsets of each RMS subtype demonstrate resistance to multimodal therapy leading to treatment failure. Cancer stem cells or cancer-initiating cells (CIC) represent a theorized population of cells that give rise to tumors and are responsible for treatment resistance. Procedure We investigated the ability of CD133, a putative CIC marker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…In our previous studies, we identified CD133-positive cells that presented typical membrane positivity in two of the most common types of pediatric sarcomas, osteosarcoma ( 5 ) and rhabdomyosarcoma (RMS) ( 6 ). The expression of CD133 in these two solid tumors, as well as the tumorigenicity of CD133-positive cells, has been confirmed by other research groups ( 7 10 ). Therefore, CD133 is currently accepted as one of the markers of a CSC phenotype in pediatric sarcomas, including RMS ( 11 – 13 ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our previous studies, we identified CD133-positive cells that presented typical membrane positivity in two of the most common types of pediatric sarcomas, osteosarcoma ( 5 ) and rhabdomyosarcoma (RMS) ( 6 ). The expression of CD133 in these two solid tumors, as well as the tumorigenicity of CD133-positive cells, has been confirmed by other research groups ( 7 10 ). Therefore, CD133 is currently accepted as one of the markers of a CSC phenotype in pediatric sarcomas, including RMS ( 11 – 13 ).…”
Section: Introductionsupporting
confidence: 75%
“…Although certain micrographs from our previous study showed cells with an accumulation of fluorescent signal for CD133 in the nucleus ( 6 ), we assumed that this finding was an artifact resulting from the use of a rabbit polyclonal antibody against CD133, (which was the only anti-CD133 antibody available at the time), although we had never detected similar nuclear positivity for CD133 in osteosarcoma or glioblastoma cell lines using the same antibody ( 5 , 18 ). Other authors investigating CD133 expression in RMS and RMS cell lines have not described the pattern of CD133 positivity in detail, and no micrographs of the individual cells are available in their published articles ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ALDH1 high cells of RH30 cells were detected, unexpectedly the ALDH1 high cells of aRMS did not form colonies or spheres (data not shown). A likely explanation of this phenomenon is that the two major RMS subtypes arise from different cells of origin, given the substantial clinical and biological distinctions between them, as reported previously by Pressey et al [ 34 ]. We are currently planning to examine whether ALDH1 can be used as a marker in other aRMS cell lines.…”
Section: Discussionmentioning
confidence: 82%
“…About 80% of aRMS are associated with chromosomal translocations generating fusion transcription factors PAX3/FOXO1 or PAX7/FOXO1 which induce expression of a specific gene expression signature. [3][4][5] While for eRMS cellular hierarchy has been recently discovered, [6][7][8] no further functional subclassification of aRMS tumor cells has been described up to date. However, current treatment approaches are only effective in a subgroup of aRMS patients with 5-year survival rate being only about 48%.…”
mentioning
confidence: 99%